Quantifying the potential for climate change mitigation of consumption options. (20th August 2020) - Ivanova, Diana; Barrett, John; Wiedenhofer, Dominik; Macura, Biljana; Callaghan, Max; Creutzig, Felix
Abstract: Background. Around two-thirds of global GHG emissions are directly and indirectly linked to household consumption, with a global average of about 6 tCO2 eq/cap. The average per capita carbon footprint of North America and Europe amount to 13.4 and 7.5 tCO2 eq/cap, respectively, while that of Africa and the Middle East—to 1.7 tCO2 eq/cap on average. Changes in consumption patterns to low-carbon alternatives therefore present a great and urgently required potential for emission reductions. In this paper, we synthesize emission mitigation potentials across the consumption domains of food, housing, transport and other consumption. Methods. We systematically screened 6990 records in the Web of Science Core Collections and Scopus. Searches were restricted to (1) reviews of lifecycle assessment studies and (2) multiregional input-output studies of household consumption, published after 2011 in English. We selected against pre-determined eligibility criteria and quantitatively synthesized findings from 53 studies in a meta-review. We identified 771 original options, which we summarized and presented in 61 consumption options with a positive mitigation potential. We used a fixed-effects model to explore the role of contextual factors (geographical, technical and socio-demographic factors) for the outcome variable (mitigation potential per capita) within consumption options. Results and discussion. We establish consumption options with a high mitigation potential measured in tons of CO2 eq/capita/yr. For transport, the options with the highest mitigation potential include living car-free, shifting to a battery electric vehicle, and reducing flying by a long return flight with a median reduction potential of more than 1.7 tCO2 eq/cap. In the context of food, the highest carbon savings come from dietary changes, particularly an adoption of vegan diet with an average and median mitigation potential of 0.9 and 0.8 tCO2 eq/cap, respectively. Shifting to renewable electricity and refurbishment and renovation are the options with the highest mitigation potential in the housing domain, with medians at 1.6 and 0.9 tCO2 eq/cap, respectively. We find that the top ten consumption options together yield an average mitigation potential of 9.2 tCO2 eq/cap, indicating substantial contributions towards achieving the 1.5 °C–2 °C target, particularly in high-income context.